FACTORS ASSOCIATED WITH TIME TAKEN TO PRESENT TO THE HOSPITAL WITH ACUTE BOWEL OBSTRUCTION: PARIRENYATWA, ZIMBABWE. - Rutsito, Locadia; Mugadza, Gladys; Kapfunde, Abigail; Rukweza, Judith; Ndaimani, Augustine (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
Tittle of the study: Factors associated with time taken to present to the hospital among patients aged 20 to 40 years with acute bowel obstruction admitted in Parirenyatwa surgical wards. Introduction: Acute small bowel obstruction is a common surgical emergency which constitutes a major cause of morbidity and financial expenditure in hospitals around the world and a significant cause of admissions to emergency surgical departments. The management method of bowel obstruction and success of the management is among other factors determined by the time taken to present to the hospital .It has been shown that those patients who present to the hospital within 24 hours from onset of symptoms have high management success rate. Aim: This research study aimed at determining the factors associated with the time taken to present to hospital among patients aged 20 to 40 years with acute small bowel obstruction in Parirenyatwa General Surgical Wards Methodology: This study utilized a quantitative, descriptive, non-experimental design. 30 participants were conveniently selected from an accessible population of men and women with acute small bowel obstruction aged 20 to 40 years admitted in PGH general surgical wards. Data was analysed using SPSS. Results: A total of 30 patients with acute small bowel obstruction participated in this research. Two (6.7%) of the participants had prior knowledge about bowel obstruction a majority (93.3%) had no knowledge about the disease till they got sick. A lager number of the participants (70%) presented late between 2 to 10 days. Lack of finance was one of the contributing factor to late presentation as expressed by (20%) of the participants. Conclusion: From this study, lack of knowledge, lack of finances and long distance to the health care facilities were the leading causes of delays in seeking medical care in acute small bowel obstruction.